Charlene Maldonado

answers: 1

Register to add an answer

Answer:

Remainder theorem:

When we divide f(x) by (x−c) , the remainder f(c)

When p(x)=4x

3

−2x

2

+px+5 is divided by (x+2), the remainder is

p(−2)=4(−2)

3

−2(−2)

2

+p(−2)+5

=−2p−35

So,

a=−2p−35

When q(x)=x

3

+6x

2

+p is divided by (x+2), the remainder is

q(−2)=(−2)

3

+6(−2)

2

+p

=p+16

So,

b=p+16

Now

a+b=0

−2p−35+p+16=0

−p−19=0

p=−19

240

Smith

For answers need to register.

100

cents

The time for answering the question is over

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions